Tetrahymenosis - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2022)
Tetrahymenosis is caused by Tetrahymena spp., a ciliated protozoa, which causes damage in various fish such as cichlid, tetras, guppy. Epidemiological data was reported in Japan, Australia and Thailand. Affected fish revealed petechial hemorrhage at body then expanded rapidly and developed deep ulcer. Moribund fish found cluster of parasite in muscles and internal organs. Treatment with medicated feed of dimetridazole showed good respond.